Pengaruh Kegiatan Ekstrakurikuler Pencak Silat Tapak Suci dalam Membentuk Akhlak Siswa di MTs. Muhammadiyah Lakitan - Dinaldi, Jihan; Ikhlas, Al (Lembaga Yasin AlSys, 2024)
This research was motivated by the decline in students’ morals. The purpose of this research is to determine the influence of Tapak Suci extracurricular activities in forming the morals of MTs students. Muhammadiyah Lakitan. This type of research is a quantitative correlation method using a simple linear regression method. The population was 576 students who took part in Tapak Suci pencak silat activities and the sample in this study was 39 people. By using a research instrument in the form of a questionnaire consisting of 20 statements, the conclusion from the results of this research was that there was an influence of Tapak Suci extracurricular activities in the formation of student morals at MTs. Muhammadiyah Lakitan. This is proven by the influence of Pencak Silat Tapak Suci extracurricular activities, that 58.8% of the moral formation variables are influenced by Pencak Silat Tapak Suci extracurricular activities in shaping the morals of students at MTs. Muhammadiyah Lakitan, the remaining 41.2% is influenced by other variables, so H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an influence of Tapak Suci extracurricular activities in forming the morals of MTs students. Muhammadiyah Lakitan.